Causes of bleeding in HRT users and non user postmenopausal women - Grzechocińska, Barbara; Gadomska, Halina; Marianowski, Longin; Dworniak, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
Introduction: Only 6% of postmenopausal women use HRT in Poland. In most cases the reason for discontinuation of HRT is the occurrence of unexpected bleeding and fear of the risk of the malignant disease as a result of the hormonal treatment. The aim of the study was to investigate the main causes of uterine bleeding in HRT users. Materials and Methods: Pathological findings from 134 postmenopausal patients with uterine bleeding were analyzed. 67 of them were using HRT. The control group consisted of 67 postmenopausal women without HRT. All bleeding women underwent medical examination; the cervical and endocervical assessment as well as uterine curettage was performed. Results: The relative risk (RR) of all abnormal results of pathological findings: endometrial cancer, cervical cancer, endometrial hyperplasia with atypia was 2.71 (95% confidence interval 1.44–3.97) in the group of women without HRT. The odds ratio (OR) of stadium secretionis endometrii, atrophia endometrii in HRT users were respectively 4.65 (95% confidence interval 0–10.77) and 2.47 (95% confidence interval 0.07–4.87). Conclusions: 1. HRT does not increase the risk of endometrial hyperplasia, particularly those complicated by atypia and uterine neoplasia. 2. Atrophic endometrial findings are more frequent in the group of HRT women.